Effectiveness of the treatment of generalized tuberculosis in HIV-infected patients - O. D. Nikolaeva (Civic Union "Communicable Diseases Intensive Care Association", 2019)
Abstract. The treatment of tuberculosis in HIV-infected persons is a complex task and often requires intensive therapy with intravenous administration of antituberculosis drugs, especially in generalized forms, malabsorption, presence of enteropathy, hepatitis B and C, severe condition. One of the dangerous forms of tuberculosis in HIV-infected people is meningeal tuberculosis. In these cases, the effectiveness of treatment for HIV-positive patients depends on timely detection, diagnosis of resistance to antituberculosis drugs, presence of other opportunistic diseases. Here is an example of treating a HIV-positive patient with miliary tuberculosis with lung damage, lymph nodes and meningeal tuberculosis caused by a multiresistant strain of tuberculosis. The treatment was performed taking into account drugs that cross the blood-brain barrier, drug sensitivity test, immunosuppression and the presence of malabsorption. Timely intensive therapy with intravenous administration of medications for medical sensitivity allowed to obtain positive dynamics and cure the patient in the short term.